Sexuality, obscenity, community : women, muslims, and the Hindu public in colonial India - Gupta, Charu (Delhi : Permanent Black ; Bangalore : Distributed by Orient Longman, 2001)
With reference to Hindu and Muslim ethics and relation to social problems; a study of Uttar Pradesh.
Includes bibliographical references (p. [345]-384) and index.
Keywords: Hindu women -- Sexual behavior -- India -- Uttar Pradesh; Sex discrimination against women -- India -- Uttar Pradesh; Women and erotica -- India -- Uttar Pradesh; Muslims -- Sexual behavior -- India -- Uttar Pradesh